Implementasi Model Pembelajaran Mordiscvein Berbantuan Media Digital Berbasis Ai Pada Mata Pelajaran Ipas Di Kelas Rendah Sdn 5 Kabila Kabupaten Bone Bolango (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This community service activity aims to implement the Mordiscvein learning model assisted by digital media based on Artificial Intelligence (AI) using Canva in the IPAS subject in the lower grades of SDN 5 Kabila Bone Bolango. The MORDISCVEIN model is the result of developing the output from a dissertation designed to enhance critical thinking skills and learning interest in elementary school students thru an interactive, creative, and contextual approach. This activity was carried out jointly with lecturers and 3A semester students of Elementary School Teacher Education at Gorontalo State University, involving 33 third-grade students. The results of the activity show that the implementation of the MORDISCVEIN model is able to increase students’ enthusiasm, active participation, and critical thinking skills thru project-based learning activities that utilize Canva as an AI-based digital medium. This activity makes a positive contribution to strengthening digital literacy and learning innovation in elementary schools. Keywords: Mordiscvein, AI, Canva, IPAS, Elementary School